Bedside vital parameters that indicate early deterioration. Issue 1 (11th February 2019) - Bunkenborg, Gitte; Poulsen, Ingrid; Samuelson, Karin; Ladelund, Steen; Akeson, Jonas
Abstract : Purpose: The purpose of this paper is to determine associations between initially recorded deviations in individual bedside vital parameters that contribute to total Modified Early Warning Score (MEWS) levels 2 or 3 and further clinical deterioration (MEWS level=4). Design/methodology/approach: This was a prospective study in which 27, 504 vital parameter values, corresponding to a total MEWS level⩾2, belonging to 1, 315 adult medical and surgical inpatient patients admitted to a 90-bed study setting at a university hospital, were subjected to binary logistic and COX regression analyses to determine associations between vital parameter values initially corresponding to total MEWS levels 2 or 3 and later deterioration to total MEWS level ⩾4, and to evaluate corresponding time intervals. Findings: Respiratory rate, heart rate and patient age were significantly ( p =0.012, p <0.001 and p =0.028, respectively) associated with further deterioration from a total MEWS level 2, and the heart rate also ( p =0.009) from a total MEWS level 3. Within 24 h from the initially recorded total MEWS levels 2 or 3, 8 and 17 percent of patients, respectively, deteriorated to a total MEWS level=4. Patients initially scoring MEWS 2 had a 27 percent 30-day mortality rate if they later scored MEWS level=4, and 8.7 percent if they did not. Practical implications: It is important to observe all patients closely, but especially elderly patients, if total MEWS levels 2 or 3 are tachypnoea and/or tachycardia related. Originality/value: Findings might contribute to patient safety by facilitating appropriate clinical and organizational decisions on adequate time spans for early warning scoring in general ward patients.